The Real inclusion: The Controversy between Inclusive Recycling and Fair Recycling in the Sustainable Development - Zárate Carabajo, Alexandra Elizabeth (2020)
This research analyses the recycling as possible business activity with view to becoming an Inclusive Business (IB) starring recyclers. The objective is determine whether the actors involved in the NI strategy under the assumption of Creation Shared Value (CSV), meet the criteria for true inclusion, which will be considered from a business and social point of view, verifying that the recycling activity is inclusive, fair and whether as IB contributes to Sustainable Development (SD). The study has a mixed approach, whit a sequential exploratory design and a non-experimental character; it was developed in the city of Cuenca (Ecuador), where 7 associations of consolidated recyclers were analyzed. A total of 161 Primary Recyclers (PRs) participated, to whom an instrument was applied; in addition, the legal framework regulating this activity was reviewed and the parameters to be met by the recycling activity were analyzed in order to be considered as NI with contribution to the SD. The results highlight the average level of inclusion of recyclers in relation to their activity. Recycling is an activity that has potential like NI, however, there are no ideal conditions, the policies and ordinances that facilitate their conceptualization and consolidation, nor does it meet the established parameters to align to the SD and contribute to the CVC.